Microstructural Characterization, Tribological and Corrosion Behaviour of Forged and Cast Grinding Balls a Comparative Study - Bouhamla, Khedidja; Gharbi, Amel; Ghelloudj, Oualid; Hadji, Ali; Maouche, Hichem; Remili, Saleh; Chettouh, Samia (Defect and Diffusion Forum, 2021)
Various facilities are used in mineral processing to prepare raw material. Practically, two types of balls are used, cast balls and forged balls. They are respectively made from high chromium cast iron and forged steel and are supplied in different sizes and chemical compositions. The cast and forged balls have different microstructures and consequently display dissimilar wear behavior. The target aimed in this work is to achieve a comparative study taking into account the type of microstructure, mechanical properties, and wear behavior of these two kinds of materials. Specimens have undergone chemical, metallographic and XRD characterizations. Subsequently, these samples were subjected to hardness measurements, abrasion and friction tests in order to evaluate their wear behaviour. Tribological tests, under unlubricated environment, are carried out on both types of grinding balls in order to study the wear system. Corrosion tests are also performed on forged steel and high chromium cast iron ball samples. The obtained results reveal a large difference in terms of chemical composition and microstructural components. Chromium cast iron balls are more resistant to friction, whereas forged balls are more resistant to abrasion. Additionally, the corrosion tests reveal a narrow discrepancy in corrosion behaviour between the studied materials.